Losses in cotton mechanized hasvest - Pereira da Silva, Rouverson (2011)
The cotton mechanized harvest is very advantageous for the collection manual, primarily because operating costs are reduced and the operation of providing the large-scale cultivation. But when the operation is not performed following criteria, can lead to losses and thus reducing gains to the farmer. This study aimed to quantify losses in the harvest of cotton in the city of Stone Ipameri-GO, in experiment conducted on three cotton properties, used the completely randomized design with 10 replications. In the three properties studied the losses in the soil out on the losses in the plant, with all properties, these losses were around 59% of total losses. Overall losses found stood at round 5.1%, 3.5% and 7.5% respectively for the three properties, remaining within the limits considered acceptable.